Complex regional pain syndrome in a middle school female field hockey player - Winkler, M. P.; Procter-Willman, C. (Journal of Athletic Training, 2019)
Background: A 15-year-old female field hockey player was transitioning into basketball season, was complaining of severe knee pain. The patient stated she was participating in the first day of basketball practice but could not continue because of the pain she was experiencing in her knee. The patient stated applying ice made the condition worse. The patient also complained of temperature and coloration changes in her knee, pain with walking on rough surfaces, and extreme sensitivity to touch. Four years prior to this injury, the patient experienced similar symptoms from a gymnastics injury in her ankle; possibly triggered from early childhood complications. Differential Diagnosis:Ankle sprain, growth plate fracture, complex regional pain syndrome/refl ex sympathetic dystrophy. Treatment:The patient underwent multiple diagnostic images including X-ray's and MRIs; all of which displayed negative results for musculoskeletal maladies. Due to continuing symptoms with no perceptible injury, the patient was referred to the neurology and pain management department. Prior to the diagnosis, the patient went through a variety of stretching exercises with the athletic trainer as prescribed by the orthopedist. Such exercises including: quadricep, hamstring, hip, and calf stretches. Once diagnosed with complex regional pain syndrome 3 months later, the patient began progressing into more aggressive and injury focused exercises with the athletic trainers. These exercises being: short arc quads, quad sets, and hip adduction squeezes. The patient also attends physical therapy weekly. The patient states that the most benefi cial therapy she does to help with her mental ability to deal with pain is mirror therapy, biofeedback, and meditations. The patient has undergone multiple nerve block shots, which she stated was more helpful than the one spinal lumbar nerve block procedure. Patient has not returned to play and will be participating in a two-week intensive inpatient physical therapy occupational program in the summer; prognosis is still unknown. Uniqueness: This type of injury is not commonly seen in the athletic population. Complex regional pain syndrome was not typically studied in children until recently. Current studies suggest approximately 90% of these cases occur in girls and between the age of 8 and 16. Conclusions: Presented was a 15-year-old female field hockey player, diagnosed with complex regional pain syndrome. The patient has undergone many procedures, and countless hours of rehabilitation; some of which has been more beneficial than others. Continuing rehabilitation and consistent moral support from the patient's providers is crucial. Since complex regional pain syndrome is a nervous system disorder, it is critical for athletic trainers to trust the patient and understand the pain they describe.